DEVELOPMENT OF PILES CARD LEARNING MEDIA FOR ARCHIVE EVALUATION - Rahma, Aulia; Marsofiyati; Rachmadania, Rizki Firdausi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
This study aims to develop a learning media based on piles card games as an evaluation instrument for archive learning in class XI Office Management (MP) of Public Vocational School 12 Jakarta and to determine the feasibility of the media based on the assessment of material experts, media experts and learning practitioners, as well as student responses. The research method used is Research and Development (RnD) with the MANTAP model, which includes five stages: Preliminary Research, Model Development, Model Validation, Effectiveness Test and Dissemination. The subjects of this study were class XI MP students. The instruments used for data collection were facilitator assessments and questionnaires for student effectiveness. Data analysis was carried out descriptively with a quantitative approach. The results of the study showed that the piles card media was feasible to be used as an evaluation instrument for Archive learning. The material expert assessor obtained an average score of 4.55, media experts 4.675, learning practitioners 4.71. Then, the responses of students from small groups were 4.8 and large groups 4.7, all of which were included in the very good category.